2019
DOI: 10.1177/1357633x19896683
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth for the internal medicine resident: A 3-year longitudinal curriculum

Abstract: Aims Across the United States of America, patients are increasingly receiving healthcare using innovative telehealth technologies. As healthcare continues to shift away from traditional office-based visits, providers face new challenges. Telehealth champions are needed to adapt technologies to meet the needs of patients, providers and communities, especially within the realm of primary care specialties. Given these challenges, this intervention aimed to incorporate telemedicine into internal medicine resident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 21 publications
0
51
0
Order By: Relevance
“…In addition to practical guidelines for those undertaking telemedicine practice, there is urgent need for the rigorous translation and evaluation of "core" trainee competencies into virtual care environments. Until recently, the majority of telemedicine curricula and learner evaluation has focused on technical proficiency or adapted history and exam skills [18][19][20] . While domains such as professionalism, communication, and other interpersonal skills are often asked of evaluators as part of a general evaluation of trainees, these domains are rarely explicitly adapted to the virtual encounter.…”
Section: Recommendations For the Training Of Residents During The Covmentioning
confidence: 99%
“…In addition to practical guidelines for those undertaking telemedicine practice, there is urgent need for the rigorous translation and evaluation of "core" trainee competencies into virtual care environments. Until recently, the majority of telemedicine curricula and learner evaluation has focused on technical proficiency or adapted history and exam skills [18][19][20] . While domains such as professionalism, communication, and other interpersonal skills are often asked of evaluators as part of a general evaluation of trainees, these domains are rarely explicitly adapted to the virtual encounter.…”
Section: Recommendations For the Training Of Residents During The Covmentioning
confidence: 99%
“…9 A 3-year internal medicine telehealth curriculum provided online didactic content and experience in remote patient monitoring. 10 Lee et al also highlighted the importance of incorporating electronic consultation in graduate medical education to improve value-based access to specialty care. 11 Although objective structured clinical examinations (OSCEs) have been used in telehealth training, most interventions are limited to single encounter e-visits at the undergraduate medical level of training.…”
Section: Introductionmentioning
confidence: 99%
“…Many residents at this clinic had no prior exposure to telehealth. A study by Kirkland and colleagues found that incorporating a three-year longitudinal telehealth curriculum for internal medicine resident physicians drastically improved resident comfort and ability to provide telehealth services [18]. This study and the low physician satisfaction with telehealth reveal the potential need to incorporate a telehealth curriculum into internal medicine resident training, especially in the COVID-19 era.…”
Section: Discussionmentioning
confidence: 74%